Growth and biochemical composition of selected algae in palm oil mill effluent / Lalitha a/p Maniam - Maniam, Lalitha (2012)
The palm oil industry in Malaysia is one of the largest producers of agroindustrial wastewater known as Palm Oil Mill Effluent (POME). POME is highly organic in content which is acidic, thick, dark in colour, with high levels of chemical oxygen demand, ammonical nitrogen, orthophosphate, nitrate, nitrite, total suspended solids, and total solids. Due to high organic load, the raw POME has to be digested anaerobically to reduce the pollutant level, in order to meet the effluent discharge standard for palm oil mills. The objective of the present study is to investigate the potential of selected microalgae to grow in POME and anaerobic liquor (AL)as well as to assess the biochemical composition of the biomass and finally the percentage of pollution reduction obtained. Nine microalgae strains from the University of Malaya Algae Culture Collection (UMACC) which are Chlorella vulgaris UMACC 001, Scenedesmus UMACC 010, Scenedesmus UMACC 036, Scenedesmus UMACC 068, Ankistrodesmus convolutus UMACC 101, Nannochloris bacillaris UMACC 109, Chlorococcum oviforme UMACC 110, Chlamydomonas augustae UMACC 246 and Chlorella UMACC 300 were screened for growth and biochemical composition using flask cultures. Of nine strains, Chlorella UMACC 300 (specific growth rate (μ) =0.35±0.02d-1 and 39.88±2.73%DW of lipid), Chlorella vulgaris UMACC 001(μ=0.32±0.02 and 40.61±2.78%DW of lipid), Scenedesmus UMACC 036 (μ=0.30±0.05d-1 and 32.75±1.01%DW of lipid) and Ankistrodesmus convolutus (μ=0.28±0.02d-1 and 38.89 ±2.70%DW of lipid) were selected to grow in different concentrations of POME and anaerobic liquor. The Chlorella UMACC 300 showed better tolerance to grow in higher concentrations of POME and AL. Chlorella UMACC 300 which grew in 25% AL (Bold Basal Medium, BBM) produce biomass of 677.33±11.37 mg L-1 with 39.98±0.38 %DW protein, 19.12 ± 0.12 %DW carbohydrate and 43.44±0.92 %DW lipid on day 16 of culture period. This Chlorella UMACC 300 also produced higher pollution reduction when compared with other three selected microalgae, whereby it attained 87.66±0.59% reduction of chemical oxygen demand (COD), 65.38±2.51% ammonical nitrogen, 78.56±6.54% orthophosphate, 45.24±4.12 % nitrate and 42.13±11.81% nitrite. The second best strain which grew in different concentrations of POME and AL was Chlorella vulgaris UMACC 001 followed by Scenedesmus UMACC 036 and Ankistrodesmus convolutus respectively. The results obtained from this study shows that Chlorella UMACC 300 which was isolated from POME is tolerant of POME and AL and may be a potential species to be used for POME and AL treatment.